PRODUÇÃO DE MATÉRIA SECA DE Eleusine coracana (L.) GAERTN. EM FUNÇÃO DA PLICAÇÃO ANTECIPADA DA ADUBAÇÃODA SOJA - Segatelli, Cláudio Roberto; Câmara, Gil Miguel de Sousa; Heiffig, Lília Sichmann; Franscisco, Eros Artur Bohac; Matos, Marcos Antonio; Pedroso, Daniel Botelho (REVISTA DE AGRICULTURA, 2015)
PRODUÇÃO DE MATÉRIA SECA DE Eleusine coracana (L.) GAERTN. EM FUNÇÃO DA PLICAÇÃO ANTECIPADA DA ADUBAÇÃODA SOJA